Psychosocial work stressors and mental health in Ph.D. students in Germany-Evidence from two cross-sectional samples. - Meike Heming; Peter Angerer; Mathias Diebig (PLoS ONE)
Background Ph.D. students have been shown to report a lower mental health status compared to the general population. However, not much is known about the impact of psychosocial work stressors that could contribute to their increased risks of mental health symptoms. This study aims firstly to assess levels of psychosocial stressors, perceived stress, and mental health symptoms in Ph.D. students. Second, it investigates which psychosocial stressors are most strongly associated with mental health symptoms and perceived stress. Methods One self-reported questionnaire was distributed among Ph.D. students at one university in Germany, in summer 2023 (T1) and winter 2023/2024 (T2). Psychosocial stressors were assessed with the short version of the effort-reward imbalance (ERI) questionnaire and with the 16-item DYNAMIK questionnaire. Mental health symptoms were assessed with the 12-item-version of the general health questionnaire (GHQ-12). Perceived stress levels were assessed with the 10-item perceived stress scale (PSS). Within a cross-sectional study design, multiple linear regression analyses were performed in two study samples (n = 267 at T1; n = 244 at T2). Results Ph.D. students reported an imbalance between effort and reward in both study samples (T1: M = 1.34, SD = 0.45; T2: M = 1.27, SD = 0.52). Effort-reward-ratio, boundary permeability, and leader support were associated with mental health symptoms and perceived stress in both study samples, when controlled for age and gender. For example, effort-reward-ratio showed a meaningful impact on mental health symptoms for the study sample at T2 (B = 3.85; p < .05, adj. R2 = 0.288). Discussion Both study samples showed high prevalence of mental health symptoms and effort-reward imbalance also in comparison to other research findings. An imbalance between effort and reward, boundary permeability and leader support show the most strongly associations with mental health symptoms and perceived stress. Future longitudinal studies could help to support our findings in terms of a causal stressor-strain association. Universities should focus on mental health of Ph.D. students and direct their support towards promoting student-supervisor relationships and clear guidelines for Ph.D. students' working hours.